Risk-adjusted chemoradiation according to human papilloma viral status for anal cancer: a pilot study - Chu, William; Taggar, Amandeep; Ung, Yee; Chan, Kelvin K. W.; Earle, Craig C.; Karotki, Aliaksandr; Pasetka, Mark; Presutti, Joe; Wong, John; Zhang, Liying; Wong, C. Shun (Frontiers in Oncology, 2023)
Background and purpose HPV-associated or positive (HPV+) anal cancer patients may have better outcome compared to those with HPV negative (HPV- disease. We report a planned interim analysis of a prospective registry study that tailors chemoradiation (CRT) for anal cancer according to HPV status. Materials and methods HPV+ patients received de-escalated radiation doses of 45, 50.4 and 55.8 Gy, while HPV- received 50.4, 55.8 and 63 Gy for T1, T2 and T3/T4 disease respectively. Chemotherapy consisted of a single dose of mitomycin-C and oral capecitabine on days of RT. All patients were planned by VMAT following CT, PET/CT and MR simulation. This cohort (n = 24) had a minimum 24-month follow-up. Disease free survival (DFS) and local failure rates (LFR) were compared with 180 patients managed by standard CRT (2 cycles of mitomycin-C and 5-fluorouracil, radiation doses 50.4-63 Gy based on T-category) from 2011-2018. Propensity score comparison was performed using a retrospective to prospective 2 to 1 match based on tumor size and N-category. Results In the HPV+ cohort (n = 20), there were 2 local failures. Two of 4 HPV- patients failed locally. The 30-month DFS and LFR were 79% and 17% respectively. Similar DFS and LFR were observed in the retrospective (80% and 15% respectively) and matched patients (76% and 16% respectively). No grade ≥3 neutropenia and febrile neutropenia were observed in the registry cohort whereas 19% and 14% respectively were seen in the retrospective patients. Conclusion De-escalation of CRT for HPV+ anal cancer may result in decreased acute toxicities and similar cancer outcomes compared to standard CRT.